Applicability of yerba-mate (Ilex paraguariensis) in different foods - Chaicouski, Adeline (2021)
Yerba-mate is a tree from South of Brazil, Paraguay, Argentina and Uruguay. Studies have demonstrated several properties with stimulating, antioxidant and anti-inflammatory action, due to bioactive compounds such as methylxanthine, saponins and phenolic compounds. The recent discoveries about these components has enabled the development of research in several areas of knowledge, such as pharmaceuticals and food. Studies have been developed with common foods becaming their into functional foods with the addition of extracts of yerba mate. The main was to carry out a bibliographic survey of the works carried out, in which yerba mate was used in the formulation of foods. Studies were found between 2003 and 2020 and the results were 34 studies. The foods developed were jelly, breads, drinks such as beer, white chocolate, cake, cereal bars, yogurt, gelatin and biodegradable films with antioxidant action in as a natural preservative in meat products. The result shows that the area of development of products based on yerba mate is promising, it is perceived that they are well formulated products and with chemical and microbiological stability.